Aluminum nanoparticles saturable absorber as a passive Q-switcher for erbium-doped fiber laser ring cavity configuration. (7th March 2019) - Salman, Ali A; Al-Janabi, A Hadi
Abstract: We report on the generation of a passively Q -switched erbium-doped fiber laser (EDFL) at 1567.6 nm, using aluminum nanoparticles (AlNPs) as a saturable absorber (SA). The synthesized film was fabricated by implanting AlNPs into polyvinyl alcohol as a host matrix. The SA thin film has a modulation depth of 7% and saturable intensity of 0.0015 MW cm −2 . A small piece of composite film was inserted between two fiber ferrules to initiate Q -switching in the EDFL. Upon reaching a pump threshold of 156 mW, a stable Q -switching was achieved. As the pump power is steadily tuned from 156–300 mW, the repetition rate changes from 34.13–48.8 kHz, while the corresponding pulse duration varies from 3.4–2.17 µ s. To the best of the authors' knowledge, this the first demonstration of passive Q -switching employing an AlNP-based saturable absorber.